Treatments for Poststroke Motor Deficits and Mood Disorders: A Systematic Review for the 2019 U.S. Department of Veterans Affairs and U.S. Department of Defense Guidelines for Stroke Rehabilitation - D'Anci, Kristen E; Uhl, Stacey; Oristaglio, Jeffrey; Sullivan, Nancy; Tsou, Amy Y (Annals of internal medicine, 2019)
Early rehabilitation after stroke is essential to help reduce disability. To summarize evidence on the benefits and harms of nonpharmacologic and pharmacologic treatments for motor deficits and mood disorders in adults who have had stroke. English-language searches of multiple electronic databases from April 2009 through July 2018; targeted searches to December 2018 for studies of selective serotonin reuptake inhibitors (SSRIs) or serotonin-norepinephrine reuptake inhibitors. 19 systematic reviews and 37 randomized controlled trials addressing therapies for motor deficits or mood disorders in adults with stroke. One investigator abstracted the data, and quality and GRADE assessment were checked by a second investigator. Most interventions (for example, SSRIs, mental practice, mirror therapy) did not improve motor function. High-quality evidence did not support use of fluoxetine to improve motor function. Moderate-quality evidence supported use of cardiorespiratory training to improve maximum walking speed and repetitive task training or transcranial direct current stimulation to improve activities of daily living (ADLs). Low-quality evidence supported use of robotic arm training to improve ADLs. Low-quality evidence indicated that antidepressants may reduce depression, whereas the frequency and severity of antidepressant-related adverse effects was unclear. Low-quality evidence suggested that cognitive behavioral therapy and exercise, including mind-body exercise, may reduce symptoms of depression and anxiety. Studies were of poor quality, interventions and comparators were heterogeneous, and evidence on harms was scarce. Cardiorespiratory training, repetitive task training, and transcranial direct current stimulation may improve ADLs in adults with stroke. Cognitive behavioral therapy, exercise, and SSRIs may reduce symptoms of poststroke depression, but use of SSRIs to prevent depression or improve motor function was not supported. U.S. Department of Veterans Affairs, Veterans Health Administration.